2018
DOI: 10.3390/rel9070215
|View full text |Cite
|
Sign up to set email alerts
|

When Children Participate in the Death Ritual of a Parent: Funerary Photographs as Mnemonic Objects

Abstract: When children lose a parent during childhood this offers emotional and life changing moments. It is important for them to be included in the death ritual and to be recognized as grievers alongside adults. Recent research has shown that children themselves consider it relevant to be part of the 'communitas' of grievers and do not like to be set aside because they are considered to be too young to participate. In this case study, I describe how a Dutch mother encouraged her three children, aged 12, 9 and 6, to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is also important to consider the psychospiritual value of personal rituals for children who are grieving. According to Faro (2018, p. 2), children want to be recognized as grievers alongside adults, though they are often excluded from funerals and other death rituals. Faro tells the story of a Dutch mother who helped her young children (6, 9 and 12 years) to participate in rituals surrounding their father’s death, and hired a photographer to document these rituals so the children could recall them later in life.…”
Section: Creating An Intersection Between Psychology and Spiritualitymentioning
confidence: 99%
“…It is also important to consider the psychospiritual value of personal rituals for children who are grieving. According to Faro (2018, p. 2), children want to be recognized as grievers alongside adults, though they are often excluded from funerals and other death rituals. Faro tells the story of a Dutch mother who helped her young children (6, 9 and 12 years) to participate in rituals surrounding their father’s death, and hired a photographer to document these rituals so the children could recall them later in life.…”
Section: Creating An Intersection Between Psychology and Spiritualitymentioning
confidence: 99%
“…Researchers from the Harvard Medical School Child Bereavement Study reported to facilitate a better grief experience for children it is important for them to 'maintain a relationship' with their parent that has died (Silverman & Nickman, 1996;; often referred to as 'continuing bonds' (Karydi, 2018). Protective factors highlighted to promote continuing bonds between a child and the recently deceased parent during the immediate bereavement period have included: listening to and sharing of stories regarding the dead parent during the wake (Haine et al, 2008), writing poems or letters and placing these inside the coffin with the parent (Faro, 2018;Holland, 2004;Mahon, 2009;Søfting et al, 2016), as well as choosing the flowers or music for the funeral service (Holland, 2004;Mahon, 2009;Søfting et al, 2016). Other studies have reported involving children in the immediate bereavement period helps them understand the finality of death (Christ, 2000) and feel valued as a family member (Søfting et al, 2016;Worden, 1996), which can help facilitate better adjustment and coping into adulthood (Christ, 2000;Faro, 2018;Fristad et al, 2000;Holland, 2004;Saldinger et al, 2004;Søfting et al, 2016;Weller et al,1988;Worden, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In short, the status of photography in research is much debated and even controversial, whatever its origin -for example, whether or not taken specifically for research, or the intentional involvement of the researcher in obtaining the photograph and its interpretation. In most situations, photography functions more as a complement or triangulation element with information collected through other techniques (Bogdan & Biklen, 1999;O'Hara & Higgins, 2017;Wang & Dong, 2013;Hamer, 2016;Faro, 2018).…”
Section: Introductionmentioning
confidence: 99%